192k views
1 vote
^Answer needed ASAP!
Solve x2-6x=-5 by completing the square. show ALL work

^Answer needed ASAP! Solve x2-6x=-5 by completing the square. show ALL work-example-1
User Site
by
4.8k points

1 Answer

7 votes

Have a nice day, be safe and healthy :)

Hope this helped

formula:

(a+b)^2

= a^2+2ab+b^2

Here, we have x^2 (as in a^2)

and -6x (as in 2ab), which, we're missing the b^2

(I'm not really sure how to describe this but bare with me)

-6/2 (-6 is from the -6x) = -3 (the b)

-3^2 = -3*-3 which is equal to 9 (positive 9)

Writing it out -

x^2-6x+9 = -5

- Addition of inequality -

Since we add 9 to the left side, we have to add 9 to the right side; which gives us:

x^2-6x+9=4

Next, lets put the x^2-6x+9 as in (a+b)^2:

(x-3)^2 = 4

Then let's do the square root of equality (square rooting both sides) :

x-3 = 2

Finally lets add 3 to both sides

x = 5

THE ANSWER IS x=5

Have a nice day, be safe + healthy - Hope this helped

User Davidsun
by
4.8k points